Augmentation of a SCADA based firewall against foreign hacking devices - Abhishek Mungekar; Yashraj Solanki; R. Swarnalatha (Institute of Advanced Engineering and Science, 2020)
An Industrial firewall is a system used to supervise and regulate traffic to and from a network for the purpose of securing appliances on a network. It analyzes the data passing through it to an already defined surveillance criteria or protocols, discarding data that does not meet the protocol’s requirements. In effect, it is a filter preventing undesirable network traffic and selectively limiting the type of transmission that occurs between a secured transmission line. In this research paper a SCADA based Firewall is implemented for protection of the data transmission to a PLC, against external hacking devices. This firewall is virtually exposed to several external hackers and the degree of vulnerability is carefully studied, in order to develop an ideal Firewall.